Manajemen Evaluasi Pendidikan Agama Islam (Kajian Ontologi, Epistimologi, dan Aksiologi) - Dedi Andrianto (Jurnal Dewantara, 2018)
Evaluation of education has a very strategic position, because the results of evaluation activities can be used as input to improve educational activities. Islamic teachings also pay great attention to these evaluations. Allah swt, in his various words in the holy book of the Qur'an and the Messenger of Allāh beberapa in some hadiths informs people, that the work of evaluating human beings is an important task in the series of educational processes carried out by educators. In other words, evaluation is a subsystem that is very important for management in every Islamic education system. In general, evaluation management of Islamic education is a systematic management based on Al-Qur'an and As-Sunnah to determine the level of success of the implementation of educational programs. Ontology study, epsitimologi, and axiology in the evaluation of learning functioned as the development of scientific paradigm about evaluation in the realm of philosophy trying to offer solutions in developing evaluation of effective and efficient learning in achieving national education goals.